Keeping the lights on [power system reliability]. - Mountford, J.D.
Of all the energy conversion processes in existence, the US electric power system is the largest and most complex. Unlike industries such as communications and transportation, where a demand in excess of supply produces a ?busy signal? or temporary grid lock, the nature of the electric power system is one of instantaneously matching supply and demand. Failure to sustain this balancing act can result in partial or complete breakdown of the grid system. In this paper, the authors describe how maintaining reliable electricity grids in a deregulated power industry will become harder, as temptations to cut corners multiply
Keywords: USA; Deregulated power industry; Electric power system; Electricity grids; Grid system breakdown; Power system reliability